Drugs are Nation’s Enemy: BNN Demanded to Implement P4GN Policy in Reducing Prevalence Rate - Kartini, Kartini; Umami, Roisatul; Putri, Aprilia Sabila; Khumayah, Siti; Imawan, Khaerudin (Green Publisher Indonesia, 2024)
The government's efforts to reduce drug trafficking in Indonesia by establishing the National Narcotics Agency (BNN), a law that regulates narcotics and rehabilitation for victims of drug abuse. This study uses a qualitative descriptive approach to investigate the implementation of the Prevention Policy for the Eradication of Abuse and Illicit Circulation (P4GN) policy by BNN Cirebon City. The research was conducted purposively, using information from the prevention division personnel and P4GN targets of school students. The results of this research can be analyzed using theory according to George C. Edward III in Saufi & Nim (2016) which explains that there are four supporting variables that affect the success of a policy, namely Communication, Resources, Disposition, and Bureaucratic Structure.